Prognostic value of positron emission tomography/computed tomography for adjuvant chemotherapy of colon cancer. Issue 6 (7th July 2017) - Baik, HyungJoo; Lee, Seok Mo; Seo, Sang Hyuk; An, Min Sung; Kim, Kwang Hee; Bae, Ki Beom; Oh, Min Kyung; Hong, Kwan Hee
Abstract : Background: To assess the prognostic value of preoperative 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography in patients with high‐risk stage II or stage III colon cancer who underwent FOLFOX chemotherapy. Methods: The study included 166 patients with high‐risk stage II or stage III colon cancer who received FOLFOX4 chemotherapy. Retrospective patient data were analysed including pathological stage, histology, disease‐free survival (DFS) and the maximum standardized uptake value (SUVmax ) of the primary tumour on 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography. The primary end point was DFS. Results: There were recurrences in 29 of the 166 patients (17.4%). Measuring the area under the receiver operating characteristic curve, the cut‐off value of SUVmax with maximum sensitivity and specificity was 10.95. Using the Kaplan–Meier method, the DFS of the patients categorized by SUVmax tended to differ ( P = 0.055). In univariate analyses, the risk factors for DFS were age over 70 years, higher N stage and neural invasion. SUVmax ≤ 10.95 showed a tendency, but was not significant ( P = 0.0604). In multivariate analyses, the risk factors for DFS were age over 70 and neural invasion. Conclusions: The results of this study suggest that high fluorodeoxyglucose uptake of the primary mass in high‐risk stage II and stage III colon cancer does not significantly correlate with DFS.